Divided by class: Government perception and political participation in Indonesia and Bangladesh - Nurlinah; Ansar, Muhammad Chaeroel; Megawati, Suci; Chowdhury, Kuntala (Frontiers in Political Science, 2025)
Political participation is a key indicator of democratic quality, yet in many developing countries, it remains unevenly distributed across social classes. While existing studies have explored government performance and political participation separately, few have examined how social class moderates the relationship between the two. This study addresses this gap by analyzing Indonesia and Bangladesh, two emerging democracies with comparable postcolonial legacies and agrarian class structures but distinct political trajectories. Using data from the Asian Barometer Survey (ABS), regression models with 780 respondents in Indonesia and 1,025 in Bangladesh are employed. Findings show that citizens from higher social classes tend to report more positive perceptions of government performance and participate more in institutional forms of politics, while lower social classes are more likely to engage in non-institutional participation driven by distrust or exclusion. These results demonstrate that social class significantly moderates the relationship between governance perception and participation type, advancing debates in comparative government and democratization by revealing how class-based inequalities shape democratic engagement in the Global South. Policy implications suggest that inclusive participation strategies must be context-specific. In Bangladesh, community-based consultation mechanisms could empower marginalized rural groups, while in Indonesia, targeted digital outreach may reduce barriers for rural lower classes. Despite these contributions, the study is limited by reliance on secondary data and the challenge of fully capturing multidimensional aspects of class beyond agrarian indicators.